Experiences of eating disorder services for people caring for a loved one with an eating disorder in the UK: national survey - Hannah Cribben; Rachel Batchelor; Pamela Macdonald; Janet Treasure; Erica Cini; Dasha Nicholls; Carol Kan (BJPsych Open)
Background Research suggests that those caring for a loved one with an eating disorder in the UK report unmet needs and highlight areas for improvement. More research is needed to understand these experiences on a wider, national scale.